Identification of ACE and HSPB8 as novel drug targets for LUSC treatment and prognosis based on a prognostic model integrating epigenetic regulation and endoplasmic reticulum stress-related genes - Yicong Zhou; Bin Wang; Changliang Song; Wenyao Xie (PLoS ONE, 2026)
Background Lung Squamous Cell Carcinoma (LUSC) remains a significant challenge in oncology due to limited diagnostic and therapeutic options. Epigenetic regulation and endoplasmic reticulum stress (ERS) play crucial roles in cancer pathogenesis, progression, and immune evasion, making them valuable areas of investigation for understanding LUSC. Methods This study integrated data from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) project to identify differentially expressed epigenetics and endoplasmic reticulum stress-related genes (EERSGs) in LUSC. Using the CIBERSORT algorithm, tumor-infiltrating immune cells were analyzed, and various machine learning and Cox models were employed to filter characteristic and prognostic markers. Further investigations included single-gene analysis, pan-cancer exploration, validation using the Human Protein Atlas (HPA) database, drug sensitivity analysis, and experimental validation through knockdown models, Western Blot, CCK-8, and Transwell experiments. Results Our analysis identified ACE and HSPB8 as potential therapeutic targets and prognostic markers in LUSC. A risk scoring system was developed, accurately predicting patient survival outcomes. Low expression groups were associated with decreased immune escape potential, indicating higher efficacy of chemotherapy and immunotherapy. Quantitative analysis of tumor-infiltrating immune cells (TIICs) and functional assays revealed significant differences in the roles of ACE and HSPB8 between normal lung and LUSC cells, underscoring their importance in tumor biology and epigenetic regulation. Conclusion This comprehensive bioinformatics and experimental study highlights ACE and HSPB8 as novel targets for LUSC treatment and prognosis, emphasizing their roles in epigenetic regulation and ERS. The risk model demonstrates preliminary potential for guiding personalized therapeutic strategies, emphasizing the need for a deeper understanding of epigenetic mechanisms and ERS in cancer development and treatment. Thus, our findings open avenues for further research into targeted therapies for LUSC, aiming to improve patient outcomes through precision medicine that considers both epigenetic factors and ERS.